Criminal records: a database for the criminal justice system and beyond - Thomas, Terry (Palgrave Macmillan, 2007)
Introduction -- A short history of criminal records -- Contemporary criminal record maintenance -- Criminal records within the criminal justice system -- The "spent" criminal record -- Criminal records and employment screening -- The criminal records bureau -- Criminal records : an international dimension -- Conclusions